Extrusion tectonism of Indochina reassessed: constraints from 40Ar/39Ar geochronology from the Day Nui Con Voi metamorphic massif, Vietnam - Dinh, Thi-Hue; Yeh, Meng-Wan; Lee, Tung-Yi; Kunk, Michael J.; Wintsch, Robert P.; McAleer, Ryan (Frontiers in Earth Science, 2023)
The extrusion tectonic model for the southeastern margin of the Himalayan orogeny links the crustal shear activity along the Red River Shear Zone (RRSZ) to the opening of the South China Sea (SCS). The Day Nui Con Voi (DNCV) metamorphic massif in northern Vietnam strikes NW-SE, is bounded by the RRSZ to the south and continues along the strike where it meets the SCS. The DNCV is thus a critical area to document thermotectonic history in order to advance our understanding of the tectonic evolution of Indochina extrusion and its relationship to the opening of the SCS. Our new 40Ar/39Ar data combined with microstructural and petrological analyses constrained the timing of the left-lateral shearing of the RRSZ and revealed the thermal evolution of the DNCV metamorphic massif. Three ductile deformation events were observed. D1 formed NNW-SSE striking upright folds under granulite to upper amphibolite facies conditions. D2 was a horizontal to sub-horizontal folding event that occurred at amphibolite facies conditions. D3 was a doming event that formed NW-SE striking up-right folds bounded by left-lateral shearing mylonite belts along the two limbs. The S/C fabrics were defined by muscovite fish, quartz + albite + K-feldspar aggregates, and muscovite folia. The D3 doming event exhumed the DNCV metamorphic massif from amphibolite facies conditions to the lower greenschist facies conditions. The 40Ar/39Ar ages obtained from amphibole (∼26 Ma), phlogopite (∼25 Ma), muscovites (∼24-23 Ma), biotite (∼25-23 Ma), and K-feldspars (∼25-22 Ma) from different structural domains of the DNCV metamorphic massif indicated a rapid exhumation ∼26–22 Ma. We interpreted this as the time period for the D3 event, with the onset of left-lateral shearing occurring around 24 Ma based on ages obtained from syn-kinematic muscovites. This age was much younger than the initiation of sea-floor spreading of the SCS (since 32 Ma) but coincided with the age for the ridge jump event in the SCS. Based on these new data, we proposed that extrusion tectonism cannot be the cause for the initial opening of the SCS. Rather, the extrusion of the Indochina block was temporally correlative with the southward ridge jump event of the already opened SCS.